The (self-)selection of international migrants reconsidered: theory and new evidence - Herbert Brücker; Cécily Defoort (Institute for the Study of Labor (IZA), 2006)
This paper reconsiders the (self-)selection of international migrants. In an extended Roy-model we analyse the factors which affect the selection bias of migrants. In particular, we find that migrants need not necessarily be (un-)favourably self-selected if the inequality of earnings is higher (lower) in the receiving country compared to the sending country. Moreover, migrants might be favourably (self-)selected if the migration costs tend to decline with the skill level of migrants, even if the inequality of earnings is larger in the destination relative to the sending country. Based on a novel data set we find descriptive evidence that migrants tend be positively (self-)selected although the inequality in earnings is higher in the sending relative to the receiving countries. Moreover, our regressions results indicate that both, a higher inequality in the host and the home country, is associated with a favourable selection bias.
Keywords: F22; 330; international migration; self-selection of migrants; human capital of migrants